Effect of Aqua Training on Cortisol and Plasma Insulin in Patients with Panic Disorder - Shiva Olamazadeh; Khosro Ebrahim; Farshad Ghazalian; Majid Barekatain (Islamic Azad University, 2016)
Introduction: Cortisol is reported to be a factor for the hypothalamic-pituitary-adrenal axis (HPA axis) in patients affected by panic disorders. On the other hand, HPA disorders can increase insulin resistance. The effect of intense aerobic exercise on the cortisol levels has also been reported on the patients with mental disorders. However, no study has yet investigated the effects of exercises in water on the cortisol and blood insulin levels in the patients affected by panic disorder. Hence, the purpose of this article was to review the effects of aqua training on cortisol and insulin levels of patients with panic disorder. Methods: Thirty six women affected by panic disorder with the average (age 38.6 ± 6.45 years and weight 70.64 ± 11.04 kg) were randomly divided in two groups of aqua training group (n=18) and the control group (n=18).The aqua training group participated in a 12-week program for water exercises (three sessions a week, each session lasting one hour, and with the intensity of 50- 85 % of maximum heart rate) and the control group continued their normal life. Pretest and posttest blood samples were taken for measuring the cortisol and blood insulin levels. Data were statistically analyzed by independent and paired sample t tests (p≤0.05). Results: The results showed that aqua training has significant effect on reduction of insulin of patients with panic disorder (p=0.001), nevertheless it has no significant effect on cortisol of patients with panic disorder (p=0.52). Conclusion: It appears that aqua training could improve the insulin levels of patients with panic disorder.